Neoadjuvant chemoimmunotherapy for esophageal squamous cell carcinoma with non-regional cervical lymph node metastasis: a retrospective pilot study - Zeng, Chufeng; Yang, Guozhen; Tan, Lingyu; Li, Kun; Zhai, Wenyu; Zhang, Xin; Liu, Longgao; Wu, Weihua; Su, Xiaodong; Fu, Jianhua; Zhang, Xu; Liu, Wei Wei (Frontiers in Immunology, 2025)
BackgroundEsophageal squamous cell carcinoma (ESCC) with non-regional cervical lymph node metastasis (CLNM) poses significant therapeutic challenges due to lack of consensus in guidelines and poor outcomes associated with conventional treatment modalities. Recent studies have demonstrated promising efficacy of combined immunotherapy, chemotherapy, and surgery in ESCC; however, the role of this multimodal approach in managing non-regional CLNM—historically considered inoperable—remains unclear.MethodsThis retrospective cohort study included 15 patients with thoracic ESCC and non-regional CLNM who underwent neoadjuvant chemoimmunotherapy (nCIT), followed by McKeown esophagectomy with three-field lymphadenectomy between 2020 and 2024. CLNM was confirmed via ultrasound-guided biopsy. Data on pathological response, safety, and survival outcomes were collected and analyzed. Survival analysis was performed using the Kaplan-Meier method.ResultsA pathological complete response (pCR) in CLNM was achieved in 93.3% of patients, while the Total pCR (ypT0N0M0) rate (clearance of both primary tumor and metastatic lymph node) was 33.3%. At a median follow-up of 18.0 months, the 1-year disease-free survival (DFS) rate was 91.7%. One patient died during the follow-up period. Postoperative complications occurred in 73.3% of patients, predominantly respiratory events such as atelectasis and pneumonia; only one patient experienced a grade 4 event. Treatment-related adverse events (TRAEs) were mild, with no grade ≥3 TRAEs observed; anemia was the most common TRAEs, occurring in 46.7% of patients.ConclusionnCIT induces a high cervical nodal response in ESCC with non-regional CLNM and may redefine surgical eligibility for patients with non-regional metastases. The observed 1-year DFS of 91.7% is promising, though long-term outcomes require further validation through prospective studies.